The Influence of Digital Promotion on Sales Enhancement for Entrepreneurs in the Textile Field through Social Media : (A Case Study in Kawalu Subdistrict, Tasikmalaya City) - Ferryan Nugraha; Heru Kurniawan (Politeknik Ganesha Medan, 2023)
Entrepreneurship is an inherent or genetic trait individuals possess, but it can also be developed through experience and education. Entrepreneurship does not always need to be cultivated intensively for individuals who have had an entrepreneurial spirit since an early age. All activities can be considered entrepreneurial activities for those with entrepreneurial talent from a young age. Entrepreneur utilizes all their abilities, such as capital, labor, and ideas, to achieve profits. Entrepreneurship plays a vital role in the economy, especially in the Micro, Small, and Medium Enterprises (MSME) sector, such as the garment industry. The growth of the garment industry in Indonesia continues to rise, along with the high demand for ready-made clothing and textile products. MSMEs, including garment production, have great potential to build economic growth. However, in the face of intense competition and increasing market demands, MSME players must have innovation, strength, thorough preparation, and adapt to the globalization trends to survive and thrive. The development of increasingly sophisticated technology has created a dependency on the Internet. Digital promotion through social media and online platforms has become an effective strategy for reaching the target market in this digital era. Digital marketing is disseminating information, persuading, and influencing purchasing decisions through digital media. Social media platforms like Instagram and Facebook are commonly used digital marketing channels. This study aims to explore the influence of digital promotion on sales in the garment business through social media. The research is conducted in the Kawalu District, Tasikmalaya City. The research methodology used is a qualitative approach involving direct interviews with garment business owners in the city. The research findings indicate that digital promotion through social media has a significant impact on increasing garment business sales. Several entrepreneurs experienced a sales increase of up to 400% after implementing digital promotion strategies.